PENGARUH KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN MENCETAK DENGAN PELEPAH PISANG - Natasa Salsa Bila; Mutia Afnida; Setiyo Utoyo; Indra Yeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
he purpose of this study was to determine the impact of banana stem printing activities on the fine motor skills of early childhood children. Instead of utilizing the natural banana stem design, the children in this study cut their own banana stems into star patterns and then used them as molds. This study used a quantitative approach with a Pre-Experiment method. The study population was 133 children, all aged 5 or 6 years, and 16 children were in the sample. The methods used to collect data were observation and testing. The methods used to analyze the data included normality tests, homogeneity tests, hypothesis tests, and effect size tests. The data obtained were processed using SPSS 30.0 for Windows to analyze the data, and set a significance threshold of 5% (0.05). The findings of this study indicate that banana stem printing activities are an effective way to help children aged five to six years hone their fine motor skills. The results showed a significant increase in children's skills between the pre- and post-treatment periods. Furthermore, the effect of this activity is included in the strong category. Kindergarten children aged five or six years have their fine motor skills greatly improved through banana stem molding exercises.